Phytobiological Characteristics of Rosa hemisphaerica Herrm. Extract - A Dehghan Kashani; I Rasooli; SM Sharafi; MB Rezaee; MR Jalali Nadoushan; P Owlia (Institue of Medicinal Plants, ACECR, 2010)
Background: Roses are one of the most important groups of ornamental plants referred to as the queen of flowers and their fruits and flowers are used in a wide variety of food, nutritional products and different traditional medicines. A large diversity is expected to be found in Iranian Damask rose landraces with different biological properties. Objective: The antibacterial, antioxidant and cytotoxicity of methanolic and aqueous extracts of Rosa hemisphaerica Herrm. were studied. Methods: The agar disc diffusion method was employed for the determination of antimicrobial activities. Total phenol contents of both extracts were estimated. Antioxidative properties of the extracts were determined by bleaching of beta carotene or 2, 20-diphenylpicrylhydrazyl (DPPH). The Ferric-Reducing Antioxidant Power (FRAP) was expressed as gallic acid equivalents. Cytooxicity of the extracts were tested using Hela and human healthy peripheral blood cells. Results: of various microorganisms tested, only S. aureus was found susceptible. The total phenol contents of the methanolic and aqueous extracts were 138.33 ± 11.37and 129.67±4.51 μg Gallic acid equivalent/mg sample respectively. DPPH scavenging and lipid peroxidation inhibition effects were higher than those of the synthetic antioxidants. Ferric-reducing antioxidant power (FRAP) of the methanolic and aqueous extracts were determined as 96.134 ± 4.25 mg/g and 98.63 ± 2.51 mg/g respectively. The 50% cytotoxic concentrations were found to be 0.327 mg/ml 0.177 mg/ml for Hela cells and human lymphocytes respectively. Conclusion: It can be concluded from the above results that R. hemisphaerica extract exhibited antimicrobial activity only against S. aureus. The extracts provided better antioxidative activity as compared with synthetic antioxidants. The extracts were toxic to the Hela cells as well as human lymphocytes. Hence, the R. hemisphaerica extract may be exploited as a natural antioxidant and health promoting agent.